IDENTIFICATION AND EXPRESSION ANALYSIS OF TWO 14‐3‐3 PROTEINS IN THE MOSQUITO Aedes aegypti, AN IMPORTANT ARBOVIRUSES VECTOR. Issue 3 (5th September 2016) - Trujillo‐Ocampo, Abel; Cázares‐Raga, Febe Elena; Celestino‐Montes, Antonio; Cortés‐Martínez, Leticia; Rodríguez, Mario H.; Hernández‐Hernández, Fidel de la Cruz
Abstract : The 14‐3‐3 proteins are evolutionarily conserved acidic proteins that form a family with several isoforms in many cell types of plants and animals. In invertebrates, including dipteran and lepidopteran insects, only two isoforms have been reported. 14‐3‐3 proteins are scaffold molecules that form homo‐ or heterodimeric complexes, acting as molecular adaptors mediating phosphorylation‐dependent interactions with signaling molecules involved in immunity, cell differentiation, cell cycle, proliferation, apoptosis, and cancer. Here, we describe the presence of two isoforms of 14‐3‐3 in the mosquito Aedes aegypti, the main vector of dengue, yellow fever, chikungunya, and zika viruses. Both isoforms have the conserved characteristics of the family: two protein signatures (PS1 and PS2), an annexin domain, three serine residues, targets for phosphorylation (positions 58, 184, and 233), necessary for their function, and nine alpha helix‐forming segments. By sequence alignment and phylogenetic analysis, we found that the molecules correspond to Ɛ and ζ isoforms ( Aeae 14‐3‐3ε and Aeae 14‐3‐3ζ). The messengers and protein products were present in all stages of the mosquito life cycle and all the tissues analyzed, with a small predominance of Aeae 14‐3‐3ζ except in the midgut and ovaries of adult females. The 14‐3‐3 proteins in female midgut epithelial cells were located in the cytoplasm. Our results may provide insights to further investigate the functions of these proteins in mosquitoes.